PENGARUH MODEL ROLE PLAYING PADA PEMBELAJARAN SENI RUPA TERHADAP HASIL BELAJAR MENGGAMBAR SISWA KELAS IV SDN 01 BASO - TETTY KHAIRIYAH, Dr. Ramalis hakin, M.Pd, Drs. Irwan, M.Sn (Universitas Negeri Padang, 2013)
The aim of this research was to know the result of students’ drawing ability that was taught by implementing role playing model. This is an experiment research that used quantitative approach. This is quasy experiment research that iused two groups that were: experiment group and control group. The population in this research was the grade IV students of Elementary School 01 Baringin Anam Baso. The data was collected by doing pre-test and post-test. The data was analyzed by using percentage form for each group, the average of students’ test, normality test, homogeneity test and hypothesis test. The finding of this research found that there is significance influence of using role playing model in teaching art and improving students’ drawing ability for grade IV students of Elementary School 01 Baringin Anam Baso. Kata Kunci: Model Role Playing dan Hasil belajar